Improving Inservice Teacher Workshops in Florida - Martha C. Monroe; Jenny Seitz; Shruti Agrawal; Sheda Morshed; Elizabeth Swiman; Michelle Aldridge; Vicki Crisp (EDIS, 2008)
Revised! FOR-109, a 5-page fact sheet by Martha C. Monroe, Jenny Seitz, Shruti Agrawal, Sheda Morshed, Elizabeth Swiman, Michelle Aldridge, and Vicki Crisp, defines the terms that are most helpful for Florida environmental education workshop facilitators and provides suggestions for planning, advertising, delivering, and evaluating workshops to better meet the needs of our teachers. Project Learning Tree (PLT) workshops are used as an example of how nonformal education facilitators could adapt their workshops to better address the new professional development system. Published by the UF School of Forest Resources and Conservation, May 2008.